Understanding Psychiatric Dimensions Related to Mental Health in Children with Special Needs: A Literature Review - Bahari, Rosyidah Rizki; Phalosa, Adelia Gian; Hikmah, Annisa Nurul; Nurmaliah, Elsa; Putri, Jeni Mediena; Yulistina, Nabila (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Children with special needs are children who possess different traits and characteristics, and they certainly require comprehensive support and care, especially in emotional aspects. Objective: The study aims to analyze the needs and services required for children with special needs to support their emotional, mental, and physical development, as well as evaluate the effectiveness of the provided support in improving their quality of life and social integration. Methods: This research uses a literature review method based on primary findings regarding children with special needs. The analysis technique used is qualitative synthesis, which combines findings from various sources to provide a deeper understanding of the topic. Results: The research shows that children with special needs have complex characteristics, categorized into specific groups as described by professionals. Some children with special needs require specialized services and attention, such as therapy with counseling, educational services, medical facilities, and family support. Conclusion: The well-being of children with special needs is influenced by several aspects of life, including healthcare services, educational and counseling services, social aspects of the community, family support, and religious aspects. Thus, the mental health dimension of children with special needs will be achieved when these aspects are adequately fulfilled.